Avaliação do uso de simulação como ferramenta complementar no desenvolvimento do mapeamento do fluxo de valor futuro - Paço, Tatiany da Rocha (Universidade Federal de São Carlos, 2006)
Nowadays companies are part of a global environment, which makes the market more competitive. In this context, the lean production system is very important for companies to become more efficient and therefore competitive. The value stream marketing is an essential tool used in the lean production system that uses an updated and a future map of process. The stationary aspect of this tool coupled with the need to obtain more accurate data highlighted the importance of computer simulations to assist in the development of value stream mapping. The present work describes all the steps of the development of a computer model in simulation software. The main aspect of it is the representation of the lean production system. The different sceneries built for the model developed in this work contributed to find the number of produced parts, dimensions of the supermarket considering the setup timing, the time of the operation, and planned or unplanned pauses of the machines. Therefore, it demonstrated that the simulation is a very useful tool to assist in the construction of the value stream mapping.
Keywords: Administração da produção; Simulação; Mapeamento do fluxo de valor; Produção enxuta; ENGENHARIAS::ENGENHARIA DE PRODUCAO